Visible light mediated selective oxidation of alcohols and oxidative dehydrogenation of N-heterocycles using scalable and reusable La-doped NiWO4 nanoparticles. Issue 16 (30th July 2021) - Abinaya, R.; Mani Rahulan, K.; Srinath, S.; Rahman, Abdul; Divya, P.; Balasubramaniam, K. K.; Sridhar, R.; Baskar, B.
Abstract : Visible light-mediated selective and efficient oxidation of various primary/secondary benzyl alcohols to aldehydes/ketones and ODH of partially saturated heterocycles using a scalable and reusable heterogeneous photoredox catalyst are described. Abstract : Visible light-mediated selective and efficient oxidation of various primary/secondary benzyl alcohols to aldehydes/ketones and oxidative dehydrogenation (ODH) of partially saturated heterocycles using a scalable and reusable heterogeneous photoredox catalyst in aqueous medium are described. A systematic study led to a selective synthesis of aldehydes under an argon atmosphere while the ODH of partially saturated heterocycles under an oxygen atmosphere resulted in very good to excellent yields. The methodology is atom economical and exhibits excellent tolerance towards various functional groups, and broad substrate scope. Furthermore, a one-pot procedure was developed for the sequential oxidation of benzyl alcohols and heteroaryl carbinols followed by the Pictet–Spengler cyclization and then aromatization to obtain the β-carbolines in high isolated yields. This methodology was found to be suitable for scale up and reusability. To the best of our knowledge, this is the first report on the oxidation of structurally diverse aryl carbinols and ODH of partially saturated N-heterocycles using a recyclable and heterogeneous photoredox catalyst under environmentally friendly conditions.